The influence of product innovation, market orientation and social media on the performance of MSMEs in the food sector in South Sumatra Province - Abidin, Zainal; Helmi, Sulaiman; Isnawijayani, Isnawijayani; Sartika , Dewi (SEAN Institute, 2024)
This research aims to investigate the influence of product innovation, market orientation and social media on the performance of Micro, Small and Medium Enterprises (MSMEs) in the food sector in South Sumatra Province. The research method used is quantitative using primary data collected through questionnaires from 70 food MSMEs who are members of the International Council of Small Business (ICSB) South Sumatra. Data analysis was carried out using Smart PLS version 4.0 software with the Partial Least Squares (PLS-SEM) approach, a variance-based structural equation analysis (SEM) method. The research results show that Market Orientation does not have a significant influence on MSME performance, while Product Innovation and social media have a significant positive influence. Analysis of variance (ANOVA) shows that together, product innovation, market orientation and social media have a significant influence on MSME performance. The conclusion of this research is that product innovation and market orientation are key factors that can improve the performance of MSMEs in the food sector. Although market orientation individually is not significant, in the overall context, all three have a significant contribution to variations in MSME performance. Therefore, MSME players in the food sector are advised to pay more attention to product innovation and market orientation as strategies for developing their business.